PENGARUH KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT AMBON MANISE INTERMEDIA - Reza Markalim; Stenly R. Titioka; Jean R Asthenu (Jurnal Administrasi Terapan, 2022)
PT. Ambon Manise Intermedia is a company engaged in mass media which has the task of finding news, compiling news and printing it in the form of newspapers and online news. To motivate employees in increasing job satisfaction at PT. Ambon Manise Intermedia was given compensation. However, several problems were still found in the distribution of compensation, such as: the provision of salaries that were still below the minimum wage, insurance that had not been implemented, unequal bonuses and limited allowances. This study aims to empirically examine the effect of compensation variables on employee job satisfaction at PT. Ambon Manise Intermedia.This research is an empirical research, with the population is all employees of PT. Ambon Manise Intermedia. The sample in this study were 31 respondents. The analysis technique used is simple linear regression analysis, in which the hypothesis test uses t-statistical test to test the partial regression coefficient with a significant degree of 0.05 or 5%. This gives the results of the t-statistical test which shows a coefficient of (0.565) with a significant value of 0.001 below the significant level of 0.05The test results on the responses of 31 respondents gave the conclusion of the study, namely, compensation has a positive and significant effect on employee job satisfaction at PT. Ambon Manise Intermedia. Based on the results of this study, it can be concluded that the research suggestions are PT. Ambon Manise Intermedia must immediately fix the problem in compensation so that employee job satisfaction increases.Keywords: Compensation, Employee Job Satisfaction